The role of talk shows in the process of democratic awareness among young people in Iraq - ahmed thamer khayoon, Asst. Prof. Dr.; Farah Ismail Dayem, Asst. Lect (lark, 2025)
role that dialogue programs play in shaping the awareness of Iraqi youth about the democratic process. In light of the political and social transformations taking place in Iraq, these programs are gaining increasing importance as platforms for dialogue, discussion, and the exchange of views on issues of democracy and good governance. The conference aims to highlight the impact of these programs in enhancing political participation among youth, developing their awareness of their rights and duties as citizens, and encouraging them to actively engage in building a sustainable democratic future.